Modelling and Simulation of the Radiant Field in an Annular Heterogeneous Photoreactor Using a Four-Flux Model - O. Alvarado-Rolon; R. Natividad; R. Romero; L. Hurtado; A. Ramírez-Serrano (International Journal of Photoenergy)
This work focuses on modeling and simulating the absorption and scattering of radiation in a photocatalytic annular reactor. To achieve so, a model based on four fluxes (FFM) of radiation in cylindrical coordinates to describe the radiant field is assessed. This model allows calculating the local volumetric rate energy absorption (LVREA) profiles when the reaction space of the reactors is not a thin film. The obtained results were compared to radiation experimental data from other authors and with the results obtained by discrete ordinate method (DOM) carried out with the Heat Transfer Module of Comsol Multiphysics® 4.4. The FFM showed a good agreement with the results of Monte Carlo method (MC) and the six-flux model (SFM). Through this model, the LVREA is obtained, which is an important parameter to establish the reaction rate equation. In this study, the photocatalytic oxidation of benzyl alcohol to benzaldehyde was carried out, and the kinetic equation for this process was obtained. To perform the simulation, the commercial software COMSOL Multiphysics v. 4.4 was employed.